2021
DOI: 10.1093/cercor/bhab202
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin Induces Aberrant Prediction Error Processing of Tactile Mismatch Responses—A Simultaneous EEG–FMRI Study

Abstract: As source of sensory information, the body provides a sense of agency and self/non-self-discrimination. The integration of bodily states and sensory inputs with prior beliefs has been linked to the generation of bodily self-consciousness. The ability to detect surprising tactile stimuli is essential for the survival of an organism and for the formation of mental body representations. Despite the relevance for a variety of psychiatric disorders characterized by altered body and self-perception, the neurobiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Notably, the extent of the P300 effect significantly correlated with the intensity of the experience of unity ('oneness with the surroundings') and changed the meaning of percepts, assessed psychometrically. Moreover, in accordance with predictive coding principles [210], psilocybin also reduced tactile mismatch processing in prefrontal cortex regions that correlated with the extent of disembodiment and changed meaning in a combined EEG-fMRT study in healthy volunteers [160]. The phenomenon of reduced mismatch processing has been interpreted as reflecting an impairment of predictive coding or, more generally, the "Bayesian brain" notion that the brain continuously updates a hierarchical model to infer the causes of its sensory inputs [162].…”
Section: Self-processingmentioning
confidence: 79%
See 2 more Smart Citations
“…Notably, the extent of the P300 effect significantly correlated with the intensity of the experience of unity ('oneness with the surroundings') and changed the meaning of percepts, assessed psychometrically. Moreover, in accordance with predictive coding principles [210], psilocybin also reduced tactile mismatch processing in prefrontal cortex regions that correlated with the extent of disembodiment and changed meaning in a combined EEG-fMRT study in healthy volunteers [160]. The phenomenon of reduced mismatch processing has been interpreted as reflecting an impairment of predictive coding or, more generally, the "Bayesian brain" notion that the brain continuously updates a hierarchical model to infer the causes of its sensory inputs [162].…”
Section: Self-processingmentioning
confidence: 79%
“…However, other studies with psilocybin [156][157][158] or DMT [159] did not reveal reductions in auditory mismatch processing. On the other hand, a recent fMRI-EEG study using a tactile mismatch paradigm revealed that psilocybin reduced the blood oxygenation level dependent (BOLD) signal responses to surprising tactile stimuli in frontal cortex regions, visual cortex, and cerebellum, as well as the electrophysiological responses in frontal cortical regions correlating with the experience of disembodiment and altered meaning of percepts [160]. Hence, it is conceivable that increased bottom-up information flow, presumably by altered cortico-thalamo-cortical gating and impaired top-down cortical integration [109,113,149], may underlie the reduced sensation of body touch and thus the experience of disembodiment [160].…”
Section: Neural Entropy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet its role in social influence processing is not understood well. Serotonergic psychedelics, such as lysergic acid diethylamide (LSD) or psilocybin (Psi), exert their psychological effects primarily via 5‐HT 2A receptor activation (Halberstadt & Geyer, 2013; Vollenweider et al, 1998; Vollenweider & Preller, 2020) and modulate mechanisms involved in emotion (Dolder et al, 2016; Kometer et al, 2012; Kraehenmann et al, 2015; Schmidt et al, 2013) and self‐relevance processing (Duerler et al, 2021; Kraehenmann et al, 2015; Preller et al, 2017; Smigielski et al, 2020; Vollenweider & Preller, 2020), therefore offering a unique opportunity to investigate the neuropharmacological mechanisms of social adaptation. Importantly, they have been shown to alter social cognition and suggestibility as well as brain activity and connectivity of the medial prefrontal cortex (mPFC), a region that is strongly involved in the processing of social information (Duerler et al, 2020; Pokorny et al, 2017; Preller et al, 2016; Preller, Schilbach, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1 ). More recently, a few multimodal neuroimaging studies combining fMRI with MEG, 84 magnetic resonance spectroscopy (MRS), 85 and EEG 86 have been also conducted. In addition, several neuroimaging studies have investigated the antidepressant of psychedelic-related drugs such as ketamine and 3,4-methylendioxymethampheamine (MDMA) in healthy subjects and clinical populations.…”
Section: Neuroimaging Of Psychedelic Effectsmentioning
confidence: 99%